2022
DOI: 10.1080/21655979.2022.2068822
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-activating protein kinase kinase kinase kinase-3, inhibited by Astragaloside IV through H3 lysine 4 monomethylation, promotes the progression of diabetic nephropathy by inducing apoptosis

Abstract: Astragaloside IV (AS-IV) is a bioactive saponin extracted from the Astragalus root and has been reported to exert a protective effect on diabetic nephropathy (DN). However, the underlying mechanism remains unclear. Herein, we found that AS-IV treatment alleviated DN symptoms in DN mice accompanied by reduced metabolic parameters (body weight, urine microalbumin and creatinine, creatinine clearance, and serum urea nitrogen and creatinine), pathological changes, and apoptosis. Epigenetic histone modifications ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Indeed, histone acetylation and methylation are implicated in the propagation of inflammation, oxidative stress and fibrosis in the kidney. Even though the exact mechanism(s) through which impaired epigenetic landscape contributes to DKD is still unclear, it appears that an altered enhancer landscape plays an important role [ 112 , 113 , 114 ]. It remains to be established whether targeting this pathway might prevent the development or delay the progression of DKD.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, histone acetylation and methylation are implicated in the propagation of inflammation, oxidative stress and fibrosis in the kidney. Even though the exact mechanism(s) through which impaired epigenetic landscape contributes to DKD is still unclear, it appears that an altered enhancer landscape plays an important role [ 112 , 113 , 114 ]. It remains to be established whether targeting this pathway might prevent the development or delay the progression of DKD.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies demonstrates that cell apoptosis is one of the major mechanisms in the development and progression of DN. Elevated apoptosis has been found in the kidneys of DN patients and suppression of the cell apoptosis in DN mice could mitigate DN symptoms (Fan et al, 2022). It was previously revealed that celastrol pre-treatment reversed HG-induced cell apoptosis to ameliorate the pathological injury of DN (Zhan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…He et al, 2023), attenuating podocyte apoptosis (Lei, Zhang, Li, et al, 2018; Xing et al, 2021; Zhang et al, 2023), alleviating renal tubular epithelial–mesenchymal transition (EMT) (X. Chen, Yang, et al, 2019; Hu et al, 2022; Y. N. Wang, Zhao, et al, 2020), and inhibiting mitogen‐activating protein kinase kinase kinase kinase‐3 (MAP4K3) (Y. Fan et al, 2022) and renal tubular epithelial cell apoptosis (Ju et al, 2019). AS‐IV administration significantly reduced urinary albumin excretion and urinary N‐acetyl‐β‐ d ‐glucosaminidase and ameliorated the renal pathologic injury in db/db mice by reducing renal dynamin‐related protein, mitochondrial fission protein 1, and mitochondrial fission factor expression and by downregulating PINK1/Parkin‐mediated mitophagy (X. Liu, Wang, et al, 2017).…”
Section: Saponins In the Treatment Of T2dm And Its Complicationsmentioning
confidence: 99%